Evaluation of left turn channelization at a signalized intersection under heterogeneous traffic conditions - Gowri, Asaithambi; Sivanandan, Ramaswamy (Transport, 2008)
The behaviour of traffic in the heterogeneous environment of an urban signalized intersection is complex and difficult to model. This paper presents the development of a simulation model to imitate the flow of heterogeneous traffic through a signalized intersection. It discusses the validation of the proposed model in terms of queue density and dissipation of vehicles at an intersection approach and found to be satisfactorily replicating the field conditions. In this study, the model was extended to examine the effects of left turn channelization on vehicle waiting times. Sensitivity analysis was carried out to study the variation of vehicle waiting times. Analysis estimated that vehicle waiting times were reduced if a channelization was provided for a high traffic volume and certain proportions of left turn vehicles in the intersection approach. The length of channelisation has marginal impacts on vehicle waiting times. First published online: 27 Oct 2010